Breastfeeding cessation and symptoms of anxiety and depression: a longitudinal cohort study - Ystrom Eivind (BMC, 2012)
Abstract Background Neonatal anxiety and depression and breastfeeding cessation are significant public health problems. There is an association between maternal symptoms of anxiety and depression and early breastfeeding cessation. In earlier studies, the causality of this association was interpreted both ways; symptoms of anxiety and depression prepartum significantly impacts breastfeeding, and breastfeeding cessation significantly impacts symptoms of anxiety and depression. First, we aimed to investigate whether breastfeeding cessation is related to an increase in symptoms of anxiety and depression from pregnancy to six months postpartum. Second, we also investigated whether the proposed symptom increase after breastfeeding cessation was disproportionately high for those women already suffering from high levels of anxiety and depression during pregnancy. Methods To answer these objectives, we examined data from 42 225 women in the Norwegian Mother and Child Cohort Study (MoBa). Subjects were recruited in relation to a routine ultra-sound examination, and all pregnant women in Norway were eligible. We used data from the Medical Birth Registry of Norway and questionnaires both pre and post partum. Symptoms of anxiety and depression at six months postpartum were predicted in a linear regression analysis by WHO-categories of breastfeeding, symptoms of anxiety and depression prepartum (standardized score), and interaction terms between breastfeeding categories and prepartum symptoms of anxiety and depression. The results were adjusted for cesarean sections, primiparity, plural births, preterm births, and maternal smoking. Results First, prepartum levels of anxiety and depression were related to breastfeeding cessation (β 0.24; 95% CI 0.21-0.28), and breastfeeding cessation was predictive of an increase in postpartum anxiety and depression ( β 0.11; 95%CI 0.09-0.14). Second, prepartum anxiety and depression interacted with the relation between breastfeeding cessation and postpartum anxiety and depression ( β 0.04; 95% CI 0.01-0.06). The associations could not be accounted for by the adjusting variables. Conclusions Breastfeeding cessation is a risk factor for increased anxiety and depression. Women with high levels of anxiety and depression during pregnancy who stop breastfeeding early are at an additional multiplicative risk for postpartum anxiety and depression.